The Challenges of the Colombian Economy for 2018 - Vallejo Zamudio, Luis Eudoro (Universidad Pedagógica y Tecnológica de Colombia, 2018)
The objectives of the economic policy for 2018 in Colombia, in relation to economic growth, unemployment, inflation and the external sector, present some favorable factors, but also uncertainty and limitations of all kinds. Regarding economic growth, the goal of 2.5 percent set for 2017 will not be achieved, since the behavior of the past three quarters indicates that it will barely reach 1.8 percent.